Terms of Citizens 'Rights Restriction when Applying Measures of Criminal Procedure Forcing - Askat, E.A. (2020)
The article considers the nature and purpose of measures of criminal procedure coercion. The authors highlighted the grounds for restricting constitutional rights and freedoms when using coercive means. The author’s definition of measures of criminal procedural coercion is formulated, which means: the preventive action applied by the authorities conducting the criminal process in the criminal case aimed at achieving the objectives of the pre-trial investigation and trial or ensuring proper conduct of the participants in the criminal process specified in the law, if any conditions and circumstances that necessitate the use of such an impact. The issues of legality and localization criteria of personal property and non-property subjective interests of citizens are raised. The analysis of the main classifications of measures of procedural coercion is carried out, and the author's approach to the classification of measures of procedural coercion is proposed, based on the conditions and the real need to limit the rights and legitimate interests of the person. Article materials can be of practical value for employees of investigative units conducting pre-trial investigations and encountering problems with the application of procedural coercive measures